RELATIONSHIP OF KNOWLEDGE AND PRAYER AGAINST BLOOD PRESSURE IN ELDERLY - Ma’mun Murod Al-Barbasy; Noor Latifah; Andriyani Andriyani; Munaya Fauziah; Nurmalia Lusida; Nurce Arifiati (Fakultas Kesehatan Masyarakat Universitas Muhamamdiyah Jakarta, 2021)
Hypertension is one of the most dominant problems in the world, both in developed countries and developing countries. Blood pressure naturally tends to increase with age. The prevalence of hypertension in Indonesia reaches 63.8% of the population aged 75 years and over. This literature review aims to determine the relationship between knowledge and prayer on blood pressure in hypertensive elderly. The benefit of this research is expected to be able to improve and provide health information in order to improve health services for the elderly suffering from hypertension. This article is a literature review by examining five journals on the relationship between knowledge and prayer on blood pressure in the elderly. The journals used are the publications of the last five years. This study was done by collecting research results from various journals, articles, and e-books. The preparation of this article took two weeks. From the results of the literature study there was a significant relationship between knowledge and prayer on blood pressure in the elderly. Therefore, it was hoped that the elderly with hypertension can seek more information about hypertension and be more obedient to pray.